Menanamkan Nilai Religius Anak Usia Dini dengan Pembelajaran Kisah Anak dalam Al-Quran - Annisa Nur; Amaliah Amaliah; Putri Salsabila (Jurnal Budi Pekerti Agama Islam, 2025)
The aim of this study is to explore how children Accounts found in the Qur'an can function as a learning medium in instilling religious values in early childhood. Religious values play a crucial role and should be familiarized with from an early stage on as a basis to foster children's character development and morals in facing life. This study uses the Observation method approach through an in-depth examination of various relevant scientific literature, including books, journals, and According to prior research, it has been shown that learning based on Qur'anic stories is effective in conveying moral and religious messages because they are in line with the imaginative aslo concrete world of children. Stories such as the Prophet Ismail, the little Prophet Yusuf, and the Ashabul Kahfi provide examples of honesty, obedience, patience, and faith that may be delivered using enjoyable approaches such as storytelling, role playing, and visualization. These findings reinforce the importance of the role of teachers and parents in internalizing religious values through contextual learning media that touch the emotional aspects of children.